Extended-spectrum beta-lactamases encoding genes among salmonella enterica serovar typhi Isolates in patients with typhoid fever from four Academic Medical Centers Lagos, Nigeria - Kabiru O. Akinyemi; Noor S.K. Al-Khafaji; Farah T. Al-Alaq; Christopher O. Fakorede; Hussein O.M. Al-Dahmoshi; Bamidele A. Iwalokun; Imaobong Akpabio; Samar Sami Alkafaas; Morteza Saki (Permanyer, 2022)
Background: There is scarce information about the occurrence of extended-spectrum β-lactamases (ESBLs) in Salmonella enterica serovar Typhi (S. Typhi) from patients with typhoid fever. Objective: To study the antimicrobial resistance and ESBL encoding genes among S. Typhi isolates in aforesaid patients from Lagos, Nigeria. Methods: S. Typhi isolates were collected from blood samples of typhoid fever patients from 4 academic medical centers in Lagos, Nigeria. The identification of isolates and their antibiotic susceptibility testing were performed by standard bacteriological techniques and disc diffusion method, respectively. The production of ESBLs was investigated using combination disk test (CDT) and polymerase chain reaction (PCR). Results: A total of 27 S. Typhi isolates was collected. All isolates were susceptible to imipenem and nitrofurantoin. Fifteen (55.6%) isolates were multidrug-resistant (MDR). The CDT test showed 11 (40.7%) ESBL producer isolates. However, the PCR revealed a higher occurrence rate for ESBL producers (66.7%, n = 18/27). The ESBL genes were as follows: blaCTX-M (37.0%, n = 10/27), blaSHV (18.5%, n = 5/27), and blaTEM (44.4%, n = 12/27). All ESBL positive S. Typhi isolates were MDR. Conclusions: This study showed the emergence of ESBL-harboring S. Typhi in patients with typhoid fever from Nigeria.